Ten years survival benefit of CABG or PCI based on individual prediction. (3rd October 2022) - Serruys, P W; Gao, C; Ninomiya, K; Hara, H; Garg, S; Onuma, Y; Kappetein, A P; Mohr, F W; Mack, M
Abstract: Background: To compare the observed and individual predicted mortalities according to the SYNTAX score II 2020 (SSII-2020) in the all-comers SYNTAX population, and retrospectively assess the appropriateness of revascularization with percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) in patients with three vessel disease (3VD) and/or left main disease (LMCAD). Methods: Internal and external validation of the SSII-2020 to predict 10-year all-cause death was performed in the respective randomized and registry SYNTAX populations. Differences in individual predicted mortalities following CABG or PCI were ranked and displayed with the observed mortalities. The proportions of screened patients deriving a survival benefit from CABG or PCI were determined retrospectively. Results: A total of 2602 participants (as-treated population) were included in the randomized and registry cohorts. In the randomized cohort, all-cause mortality at 10 years, as an average treatment effect, was 23.8% (199/865) with CABG and 28.6% (249/901) with PCI, with a differential survival benefit of 4.6% (95% CI: 0.58% to 8.7%, log-rank p value=0.023). In the CABG and PCI registries, mortalities were 27.8% (167/644) and 55.4% (99/192), respectively. Calibration and discrimination of the SSII-2020 was helpful in CABG and PCI patients in the randomized and registry cohorts. In the PCI registry, the SSII-2020 underestimated mortality since specific comorbidities that entail high mortality are not included in the formula (C-index: 0.72, intercept: 0.38, slope: 0.66), whilst in the CABG registry, it predicted mortality with a helpful calibration and discrimination (C-index: 0.70, intercept: 0.00, slope: 0.76). The proportions of patients with a predicted survival benefit following CABG and PCI were respectively 78.3% (1383/1766) and 21.7% (383/1766) in the randomized cohort, and 82.4% (2143/2602) and 17.7% (459/2602) in the whole SYNTAX trial population. Conclusion: In the randomized and registry cohort of this all-comers population with 3VD and/or LMCAD, there was reasonable agreement between the individual predicted and observed mortalities after CABG or PCI, such that the predicted 10-year survival benefit might be helpful in determining the appropriateness of each modality of revascularization. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): The SYNTAX Extended Survival study was supported by the German Foundation of Heart Research (Frankfurt am Main, Germany). The SYNTAX trial, during 0-5 years follow-up, was funded by Boston Scientific Corporation (Marlborough, MA, USA). Both sponsors had no role in the study design, data collection, data analyses, and interpretation of the study data, nor were involved in the decision to publish the final manuscript. The principal investigators and authors had complete scientific freedom.